Oral Kaposi's sarcoma: Sole presentation in HIV seropositive patient - Arul, A. Sri Kennath J. (J Nat Sci Biol Med, 2015)
Acquired immunodeficiency syndrome (AIDS)-associated Kaposi's sarcoma (KS) occurs with increased frequency in all HIV transmission groups and at a particularly high rate among homosexual men. It usually presents initially as violaceous cutaneous lesions, but oral mucosa, lymph nodes and visceral organs may be affected, sometimes without skin involvement. KS in a 20-year-old HIV-seropositive patient with oral involvement as the sole presentation of the disease is presented herewith; thus contributing a new AIDS-related KS case reported in Indian Literature.